Cost-effectiveness of pre-emptive pharmacogenetic testing: An umbrella review - Taichi Ochi; Manon G. den Uil; Greta Piazza; Geert W. J. Frederix; Eelko Hak; Vera H. M. Deneer; Talitha L. Feenstra (PLoS ONE, 2026)
Background Consortia have been established and published pharmacogenetic-specific guidelines with pharmacotherapeutic recommendations. While these consortia and their guidance addressed important information gaps, implementation barriers, including determining the cost-effectiveness for further implementation in healthcare practice, remain unaddressed. Methods The authors systematically searched PubMed, EMBASE, and Web of Science from inception to March 2023 for systematic reviews of pharmacoeconomic evaluations of PGx studies. A second search was conducted in October 2025. The studies from the databases were imported into Rayyan for screening the title and abstract, based on the inclusion and exclusion criteria. The umbrella review was conducted in adherence to the proposal registered in PROSPERO (CRD42023408535). The quality of eligible systematic reviews was assessed by the AMSTAR-2 checklist. Results From the initial screening of the three databases, title and abstract screening, and full paper readings, 17 systematic reviews were included for the umbrella review. The evidence points to the fact that with an increasing number of evaluations, the evidence for the cost-effectiveness of PGx testing was increasing over the years. From the included reviews, data from 211 unique evaluation studies were extracted. 150 (71.1%) studies reported that PGx testing was cost-effective. The most frequently used type of economic evaluation was cost-utility analysis (n = 78). Most economic evaluations investigated the pharmacogene CYP2C19 (n = 46), followed closely by CYP2C9/VKORC1 (n = 28). Conclusions The number of economic evaluations demonstrating cost-effectiveness of PGx testing has increased over the years. However, the majority of these evaluations were conducted in a small number of countries. When interpreting findings for different countries, the evaluations need to be adjusted on a case-by-case basis for applicability.